Comprehensive Diagnostic Medical System Based on Notch1 Signaling Pathway to Inhibit the Growth of Small-Cell Lung Carcinoma. (19th May 2022) - Zhang, Xiaoli; Yu, Ziying
Abstract : With the gradual application of big data and other technologies to the medical field, more and more people tend to get online medical services. This article mainly studies the comprehensive diagnostic medical system based on Notch1 signaling pathway to inhibit the growth of small-cell lung carcinoma. In the experiment, we used the rapid thawing method to recover the cells and took the logarithmic growth phase cells for cell passage. We calculated the cell concentration and diluted the cells according to the experimental requirements. According to the standard curve, the corresponding sample protein concentration was calculated; at the same time, the Trizol method was used to extract the total RNA, the NanoDrop8000 spectrophotometer was used to determine the RNA concentration, and the RNA quality was detected by agarose gel electrophoresis. We used immunohistochemical staining to complete the staining of lung cancer cells. Finally, black box testing was used to test the functional modules of the system. Experimental data show that the accuracy rate of data obtained by the system reaches 98%, which greatly facilitates doctors and patients. The results show that the system has good ease of use and reliability and improves the diagnosis and treatment of hospital patients.